Implementation of Law of the Republic of Indonesia Number 20 of 2001 Concerning Amendments to Law Number 31 of 1999 Concerning the Eradication of Corruption Crimes Against Selection Bribery Cases Independent Pathway Students - Supiyan Supiyan; Bernat Panjaitan; Nimrot Siahaan (Journal of Social Research, 2023)
This study aims to find out and analyze the phenomenon of bribery cases for independent path student selection and find out and analyze about the factors causing and impacting corruption. This research belongs to the normative type of research. So it can be known that the act of bribery in the phenomenon of bribery cases of independent track students has a damaging impact that is as bad as the criminal act of bribery bribery that occurs in the public domain, so it is necessary to take concrete steps to criminalize the act of bribery. Bribery as stipulated in the UUTPK is very diverse, the threat of criminal penalties and fines regulated in it also varies, causing legal uncertainty in law enforcement and contrary to the principle of legality. In addition, corruption is caused by many factors, both political, legal, economic, organizational, and cultural. Economic factors, such as low salaries, losses suffered, poverty, and others are often considered the dominant factors.